2017
DOI: 10.1002/anie.201701724
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Ion Conduction in Methylammonium Lead Iodide: A Multimethod Approach

Abstract: By applying a multitude of experimental techniques including 1H, 14N, 207Pb NMR and 127I NMR/NQR, tracer diffusion, reaction cell and doping experiments, as well as stoichiometric variation, conductivity, and polarization experiments, iodine ions are unambiguously shown to be the mobile species in CH3NH3PbI3, with iodine vacancies shown to represent the mechanistic centers under equilibrium conditions. Pb2+ and CH3NH3 + ions do not significantly contribute to the long range transport (upper limits for their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
305
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 238 publications
(338 citation statements)
references
References 51 publications
33
305
0
Order By: Relevance
“…[1] Despite such high PCEs, poor long-term stability of mp-TiO 2 based PSCs is a problematic issue for commercialization. [14,15] It has also been demonstrated that oxygen induces photodegradation of methylammonium lead iodide (MAPbI 3 ). [13] The long-term operational stability of 1000 h in BaSnO 3 -based PSCs was realized only in a laminate cell.…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
“…[1] Despite such high PCEs, poor long-term stability of mp-TiO 2 based PSCs is a problematic issue for commercialization. [14,15] It has also been demonstrated that oxygen induces photodegradation of methylammonium lead iodide (MAPbI 3 ). [13] The long-term operational stability of 1000 h in BaSnO 3 -based PSCs was realized only in a laminate cell.…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
“…Since the distance between the HaP incorporated in the TiO 2 and the TiO 2 nanoparticles is very small, more strongly doped materials such as MAPbBr 3 (Cl) and CsPbBr 3 should have a stronger net electric field compared to the more intrinsic materials (MAPbBr 3 , (FA,MA,Cs)PbBr 3 ). [39,40] If these two properties, alone or together, are the ones that are responsible for the observed hysteresis in MAPbI 3 -based devices [and in (FA,MA,Cs)PbBr 3 as seen in Figure 1], it can indicate that ion migration is more dominant in the mixed cation layers than in the single cation devices, possibly because of a less closely packed lattice in the former (where a c = 6.00 Å) than in the MAPbBr 3 (cf. To visualize this, we plot in Figure 4 the normalized EBIC collection efficiency versus the mp-TiO 2 \HaP area for the four different HaP devices that were considered in Figure 2.…”
Section: Doi: 101002/aenm201800398mentioning
confidence: 99%
“…Optoelectronic properties of perovskites, including large absorption coefficient, long diffusion length, long carrier lifetimes, and high tolerance of defects, have been confirmed to influence halide‐based perovskite device performance . Since perovskite is a mixed carrier‐ionic conductor, perovskite‐based devices are significantly affected by the dynamics of mobile ions . Mixed‐halide perovskites with tunable bandgaps enable bandgap engineering in tandem solar cells and multiple‐color LED .…”
mentioning
confidence: 99%